9514 1404 393
Answer:
m = (5x -6)/(43y -4)
Step-by-step explanation:
Subtract 4m+6 to separate m-terms from other terms.
5x +4m -(4m +6) = 43my +6 -(4m +6)
5x -6 = 43my -4m
5x -6 = m(43y -4) . . . . factor out m
(5x -6)/(43y -4) = m . . . . divide by the coefficient of m
Answer:
6 + 4 × -2/4 = 4
Step-by-step explanation:
hi hope u understand
Answer:
Answer:y=2/3x-10/3
- 4/-6 is 4/6 so m is 4/6 then fill in the x and y variables in y=Mx+b solve for b then start plotting the equation of the line to check and you get your answer
I think this is the answer you might need to check again with more people
Step-by-step explanation:
I did it wrong the first time you're answer is b. 11*11^4